Retroperitoneal Immature Teratoma in a Neonate - Chiranjiv Kumar; Rajpal Singh Sisodiya; Shasanka Shekhar Panda; Yogesh Kumar Sarin (EL-Med-Pub, 2017)
We report a rare case of large immature retroperitoneal teratoma in a neonate. The diagnostic and therapeutic challenges of dealing with such a case have been discussed and the relevant literature reviewed.